Nation-building and foreign policy in India: an identity-strategy conflict - Engelmeier, Tobias (Foundation Books, 2009)
Nation-Building and Foreign Policy in India: An IdentityStrategy Conflict presents an evaluation of Indian foreign policy. It analyses the unusual concern of Indian strategic thinking about political values. The book argues that in Indian foreign policy, there has been a shift from a strict concern for national interest towards idealist considerations. Thus creating what the author calls an idealist inflection. This inflection does not have its roots in cultural aspects or grand strategy. Instead, it is best understood with reference to the political process of nation-building, characterised by the specific choices and decisions taken by the two leading protagonists of the Indian National Movement Mohandas Karamchand Gandhi and Jawaharlal Nehru. The values they chose to place at the heart of Indias national identity have spilt into the countrys foreign policy
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: India -- Foreign relations -- 1947-1984; India -- Foreign relations -- 1984-; Außenpolitik; Nationenbildung; Indien